Digital Budgeting And Fiscal Transparency In Local Governments: The Mediating Role Of Public Accountability - Okto Irianto; Andi Matuladda; Caecilia Henny Setya Wati (Academic Bright Collaboration, 2026)
Purpose –This study examines the direct and indirect relationships among digital budgeting, leadership commitment, public accountability, and fiscal transparency in local government institutions in Merauke Regency, Indonesia as a developing-region context where empirical research on integrated fiscal transparency mechanisms remains limited. Methods – A quantitative design was employed using a structured questionnaire administered to 105 structural officials across 15 Local Government Agencies (OPD) in Merauke Regency, selected through multi-stage purposive sampling (n = 105; population = 288). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Common method variance was assessed via Harman's single-factor test (largest factor = 28.4%), and model fit was confirmed (SRMR = 0.067). Findings – Digital budgeting significantly affects public accountability (β = 0.41) and fiscal transparency (β = 0.28), while leadership commitment significantly affects public accountability (β = 0.36) and fiscal transparency (β = 0.25). Public accountability exerts a significant effect on fiscal transparency (β = 0.39) and mediates both antecedent relationships with fiscal transparency (indirect effects: β = 0.16 and β = 0.14, respectively). The model explains 52% of variance in public accountability (R² = 0.52) and 63% in fiscal transparency (R² = 0.63). Research implications – Improving fiscal transparency requires the concurrent development of digital financial systems, strong leadership commitment, and robust accountability mechanisms. Local governments are advised to treat accountability framework strengthening as a priority alongside, rather than subsequent to, digital system investment. Originality – This study advances public sector accounting literature by developing an integrated structural model that simultaneously examines the technological and organizational determinants of fiscal transparency in a developing-region local government context, demonstrating the mediating role of public accountability across both antecedent pathways.